Haar Wavelet Collocation Method For Solving Boundary Layer Flow And Heat Transfer Over A Moving Plate In A Carbon Nanotubes With Mhd Effect - Haswaniza N. S.; Rasedee A. F. N; Bachok N.; Wong T. J.; Hasan M. (2026)
Indexed by SCOPUS